Strategi Pemasaran Produk Indosat M3 di Kota Kediri Berdasarkan Analisis SWOT - Komari, Ana (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2016)
The business world of telecommunications is now a full decade with the changes that are filled with newcomers in the business world of telecommunications. The changes and upheavals are not just fast, unpredictable and complex, but also contradictory and could lead to a crisis (Pierce & Robinson, 1994). To respond to these changes companies need to fundamentally rethink their strategy, structure, performance in order to have the ability to compete in the increasingly fierce competition conditions. The company is required to continuously adjust its strategic planning related to the company business environment so that the chosen strategy is always appropriate. In order to find the appropriate marketing strategy formulation then it is needed efforts to identify the strengths, weaknesses, opportunities and threats faced by the company. For those reasons, this study was held which focused on the determination efforts of the marketing strategy that appropriate with the company condition in the middle of competition. Research conducted in Indosat M3 in particular on its Smart product used a qualitative method by using respondent of employees who have an understanding of the market conditions that amounted to 15 people. Data collection tool used was a structured questionnaire with closed-type questions. The results of this study indicated that the strategy formulation suggested for Indosat M3 Smart is an investment strategy by emphasizing on distribution and pricing strata such as make empowering potential outlets, cooperate with Bank Mandiri and BCA, as well as the incentives system for the interesting channeling. Thus, Indosat M3 Smart products can feature their competitive advantage if compared to other similar competitors. Keywords: IM3, Telecommunications, Marketing Strategy, SWOT Analysis.